Oxide scintillators to search for dark matter and double beta decay - Nagomaya, L; Danevich, F; Dubovik, A; Grinyov, B; Henry, S; Kapustyanyk, V; Kraus, H; Poda, D; Mokina, V; Mikhailik, V; Panasyuk, M; Polischuk, O; et al. (2008)
Results are presented of our latest research, aimed at the development and study of oxide scintillation crystals with high scintillation yield and low intrinsic radioactivity. We report on the improvement of these properties for conventional scintillators, as well as on new promising crystals based on metal tungstates and molybdates. The results are discussed in view of applying these materials in cryogenic experiments searching for dark matter or neutrinoless double beta decay. ©2008 IEEE.